2006
DOI: 10.1162/jocn.2006.18.4.594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on BOLD fMRI during Prosaccades and Antisaccades

Abstract: Age affects the ability to inhibit saccadic eye movements. According to current theories, this may be associated with age-induced neurophysiological changes in the brain and with compensatory activation in frontal brain areas. In the present study, the effects of aging are assessed on brain systems that subserve generation and inhibition of saccadic eye movements. For this purpose, an event-related functional magnetic resonance imaging design was used in adults covering three age ranges (18-30, 30-55, and 55-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
6
54
3
Order By: Relevance
“…Widespread involvement of a frontoparietal control network has been reported in healthy young adults during the preparation of saccadic movement and is consistent with the regions of interest investigated in the current study (Curtis and Connolly, 2008; Ford et al, 2005). Notably, Raemaekers and colleagues (Raemaekers et al, 2006) conducted an AS fMRI study across three age ranges from 18 to 72 years and found that healthy adults recruited more frontal oculomotor regions with increasing and advanced age, supporting our conclusion that frontal regions, such as the rlatFEF and rDLPFC, are critical network hubs for AS performance and may be selectively vulnerable with age. Because the previous study did not identify a significant relationship between regional BOLD signal and AS task performance in individual subjects, our study provides new insights into the underlying mechanisms responsible for the elevated BOLD signal in older individuals.…”
Section: Discussionsupporting
confidence: 83%
“…Widespread involvement of a frontoparietal control network has been reported in healthy young adults during the preparation of saccadic movement and is consistent with the regions of interest investigated in the current study (Curtis and Connolly, 2008; Ford et al, 2005). Notably, Raemaekers and colleagues (Raemaekers et al, 2006) conducted an AS fMRI study across three age ranges from 18 to 72 years and found that healthy adults recruited more frontal oculomotor regions with increasing and advanced age, supporting our conclusion that frontal regions, such as the rlatFEF and rDLPFC, are critical network hubs for AS performance and may be selectively vulnerable with age. Because the previous study did not identify a significant relationship between regional BOLD signal and AS task performance in individual subjects, our study provides new insights into the underlying mechanisms responsible for the elevated BOLD signal in older individuals.…”
Section: Discussionsupporting
confidence: 83%
“…The fact that the area of striate cortex does not decrease with age is consistent with previous research, 7,23 and reductions in BOLD activity without corresponding changes in cortical volume have been demonstrated in other areas of the visual and motor systems. 11,12 It has previously been shown that neural deficits are responsible for the poorer vision of older observers, 8 -10 and indeed our older subjects did have lower visual acuity and contrast sensitivity than our younger volunteers (mean visual acuity: older observers, Ϫ0.03 logMAR; younger observers, Ϫ0.19; P Ͻ 0.01; mean contrast sensitivity: older observers, 1.79 log units; younger observers, 1.95 log units; P Ͻ 0.05). However, changes in contrast sensitivity are not enough to account for the differences in the cortical activity (r 2 ϭ 0.11; P ϭ 0.35).…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 Anatomic and histologic studies can determine the number of neurons present, but to determine the activity of these neurons, a functional imaging technique such as fMRI is required. This approach has been used to determine the effects of age on tasks such as saccade control, 11 motor performance, 12 and memory. 13 We used this technique to measure the BOLD response of neurons in V1 to visual stimulation.…”
mentioning
confidence: 99%
“…Raemaekers et al (2006) investigated age-related changes in brain activation during saccade tasks using fMRI. However, that study did not reveal clear differences between young and elderly adults, suggesting the methodological limitations of fMRI.…”
Section: Eye Movement Performance and Prefrontal Hemodynamics During mentioning
confidence: 99%